PERANCANGAN ALAT UKUR TDS (TOTAL DISSOLVED SOLID) AIR DENGAN SENSOR KONDUKTIVITAS SECARA REAL TIME - Zamora, Ronaldi; Harmadi, Harmadi; Wildian, Wildian (IAIN Batusangkar, 2015)
An experiment was done to design of conductivity sensor for real time measurement of TDS (Total Dissolved Solid) in water. The instrument system incluedes hardware and software systems. The hardware system consist conductivity sensor, microcontroller arduino uno, and a PC. While the software system covers the procces and making on display measurement result based on LabVIEW. TDS information is displayed in the form of digital, analog and graph in real time. Another advantage of this measurement system is that the TDS data can be stored in file format xlxs. The measurement data is done by comparing the system is designed with a standard measuring instrument that is TDS EZDO E 7200. The data obtained through measurement errors were analyzed using the theory and methods of the graph. Based on the analysis conducted found the output voltage of the conductivity sensor rises with the increase in water with a sensitivity of 0,924 mV/ppm. The instrument of TDS measurement data has an accuracy rate of 97.17 %Keyword: microcontroller, water, TDS, LabVIEW